Predictors of Relapse in Idiopathic Nephrotic Syndrome in Children Presenting to a Tertiary Center - Akter, A.H.M Muslima; Muinuddin, Golam; Rahman, Md. Habibur; Roy, Ranjit Ranjan; Begum, Afroza Begum; Huque, Syed Saimul; Jesmin, Tahmina; Rahman, Md. Azizur (Journal of Pediatric Nephrology, 2020)
Background and Aim: Idiopathic nephrotic syndrome (INS) is a disease of relapse and remission in children in which about 20-30% of the patients may experience a single episode in their lives while the rest suffer from relapse. Some factors contribute to relapse. The objective of this study was to explore the predictors of relapse in INS. Methods: A prospective longitudinal study was conducted in the Department of Pediatric Nephrology, Bangabandhu Sheikh Mujib Medical University (BSMMU) from September 2015 to August 2016. One hundred and ten patients with the first episode of INS were uninterruptedly enrolled in this study. After screening and subsequent confirmatory diagnosis, the patients were treated with a single morning dose of oral prednisolone 60 mg/m2/day for 6 weeks followed by oral prednisolone 40 mg/m2 every alternate day for the subsequent 6 weeks. The total number of relapses within six months after the initial episode was collected in a data collection sheet. Every relapse was correlated with age of onset, sex, initial serum albumin level, fasting serum cholesterol level, and time to response in the initial attack. The association between relapse and its potential risk factors was investigated using logistic regression analysis. Results: The study found that INS was significantly associated with sex and age (p< 0.05). Male children were 3.04 times (95% CI= 1.09- 8.45, P=0.03) more likely to experience relapse. Furthermore, children with respiratory tract infection had a higher chance of relapse (OR= 4.43, 95% CI= 1.26-15.53, P=0.02). Lower cholesterol levels (≤500 mg/dl) were found to be a protective factor (OR= 0.13, 95% CI= 0.04-0.54, P=0.005) in this study. The chance of relapse was higher in children who responded after 2-4 weeks of starting treatment compared to those who responded in less than one week (p<0.005). Conclusion: The study found that the first episode INS had a higher risk of relapse in boys with respiratory tract infection and in patients who needed more than two weeks of prednisolone treatment to achieve remission. Keywords: Children; Frequently Relapsing; Predictors; Idiopathic Nephrotic Syndrome.